Cascaded spiral microfluidic device for deterministic and high purity continuous separation of circulating tumor cells - Kim, Tae Hyun (Biomicrofluidics, 2014)
Inertial microfluidics is an emerging class of technologies developed to separate circulating tumor cells (CTCs). However, defining design parameters and flow conditions for optimal operation remains nondeterministic due to incomplete understanding of the mechanics, which has led to challenges in designing efficient systems. Here, we perform a parametric study of the inertial focusing effects observed in low aspect ratio curvilinear microchannels and utilize the results to demonstrate the isolation of CTCs with high purity. First, we systematically vary parameters including the channel height, width, and radius of curvature over a wide range of flow velocities to analyze its effect on size dependent differential focusing and migration behaviors of binary (10 μm and 20 μm) particles. Second, we use these results to identify optimal flow regimes to achieve maximum separation in various channel configurations and establish design guidelines to readily provide information for developing spiral channels tailored to potentially arbitrary flow conditions that yield a desired equilibrium position for optimal size based CTC separation. Finally, we describe a fully integrated, sheath-less cascaded spiral microfluidic device to continuously isolate CTCs. Human breast cancer epithelial cells were successfully extracted from leukocytes, achieving 86.76% recovery, 97.91% depletion rate, and sustaining high viability upon collection to demonstrate the versatility of the device. Importantly, this device was designed without the cumbersome trail-and-error optimization process that has hindered the development of designing such inertial microfluidic systems.